From lab to industrial development of lipid nanocarriers using quality by design approach - Aristote B. Buya; Phindile Mahlangu; Bwalya A. Witika (International Journal of Pharmaceutics: X, 2024)
Lipid nanocarriers have attracted a great deal of interest in the delivery of therapeutic molecules. Despite their many advantages, compliance with quality standards and reproducibility requirements still constrain their industrial production. The relatively high failure rate in lipid nanocarrier research and development can be attributed to immature bottom-up manufacturing practices, leading to suboptimal control of quality attributes. Recently, the pharmaceutical industry has moved toward quality-driven manufacturing, emphasizing the integration of product and process development through the principles of quality by design. Quality by design in the pharmaceutical industry involves a thorough understanding of the quality profile of the target product and involves an assessment of potential risks during the design and development phases of pharmaceutical dosage forms. By identifying essential quality characteristics, such as the active ingredients, excipients and manufacturing processes used during research and development, it becomes possible to effectively control these aspects throughout the life cycle of the drug. Successful commercialization of lipid nanocarriers can be achieved if large-scale challenges are addressed using the QbD approach. QbD has become an essential tool because of its advantages in improving processes and product quality. The application of the QbD approach to the development of lipid nanocarriers can provide comprehensive and remarkable knowledge enabling the manufacture of high-quality products with a high degree of regulatory flexibility. This article reviews the basic considerations of QbD and its application in the laboratory and large-scale development of lipid nanocarriers. Furthermore, it provides forward-looking guidance for the industrial production of lipid nanocarriers using the QbD approach.